Perkembangan Islam dan Gerakan Politiknya di Malaysia - Rohman, Abdul (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) UIN Walisongo, 2020)
Islam entered the territory of Malaysia, especially in the Malacca kingdom, through Muslim merchants from India and Arab-Persia around the 7th century AD The broad development took place around the 13th century, with the discovery of inscriptions nuanced by Islam. Islamic political thought and movement was more intensive since the struggle for political compromise to gain independence from British colonialism. The Islamic political movement has a spectacular momentum when the Malaysian Constitution places Islam as the official religion of the state and makes ethnic Malays as a special group (special privileges) over other ethnic groups. The development of Islam is supported by an Islamic political movement that is controlled by political parties holding power, namely UMNO, even though Islam is inclusive and upholds the value of nationalism, its work still prioritizes Islamic values. Opposition parties such as PAS which are more fundamaentalist in their ethical sense have actually been adopted by the ruling party. This means that the two parties benefited the existence of Islam. Referring to the peaceful Islamic political movement in order to uphold the teachings of Islam in Malaysia, both legally and formally and constitutionally and culturally, it can be an inspiration to other Muslim-majority countries.